A High Air‐Stability and Li‐Metal‐Compatible Li3+2xP1−xBixS4−1.5xO1.5x Sulfide Electrolyte for All‐Solid‐State Li–Metal Batteries - Ni, Yu; Huang, Chao; Liu, Hong; Liang, Yuhao; Fan, Li‐Zhen (Advanced functional materials, 2022)
All‐solid‐state batteries are one of the most promising lithium–ion batteries as they are safe with high energy density and applicable to different occasions. Sulfide solid electrolytes (SSEs) are welcoming due to their good ionic conductivity and processability. However, as the SSE conductor is unstable when exposed to air, its development and application are limited. A series of new Li3+2xP1−xBixS4−1.5xO1.5x (X = 0.02, 0.04, 0.06, 0.08) solid electrolytes are synthesized by co‐doping Li3PS4 with Bi and O, and the new electrolytes have better ionic conductivity and air‐stability than Li3PS4. The lithium ionic conductivity of Li3.12P0.94Bi0.06S3.91O0.09 solid electrolytes reached up to 2.8 mS cm–1 at room temperature, the highest and 9 times as high as that of Li3PS4. The doped solid electrolytes are compatible with lithium anode, and the cycling performance is improved. Importantly, the critical current density of Li3.12P0.94Bi0.06S3.91O0.09 electrolytes can reach to 1.2 mA cm–2. In particular, the Li|Li3.12P0.94Bi0.06S3.91O0.09|Li symmetric cells are stable even after 400 h running at 1 mA cm–2 and 25 °C. Bi2O3 doping SSEs are expected to be the next generation of all‐solid‐state lithium batteries due to their good ionic conductivity and air‐stability. Herein, the Li3.12P0.94Bi0.06S3.91O0.09 is synthesized successfully via Bi, O co‐doping the Li3PS4 for the first time. Compared with the pristine Li3PS4 electrolyte, the co‐substitution Li3.12P0.94Bi0.06S3.91O0.09 electrolyte presents higher Li+ ions concentration, excellent structural stability, admirable air stability, and ultrahigh critical current density.